PROSES INDUSTRIALISASI DI INDONESIA DALAM PRESPEKTIF EKONOMI POLITIK - Damayanthi, Vivin Retno (Journal of Indonesian Applied Economics, 2008)
Industrialization  has  become  one  of  the  economic  transformation  programs  inIndonesia. There are many policies implemented to support the programs. This paperwill observe the process of industrialization in Indonesia in the perspective of politicaleconomy. Furthermore, it also will analyze on how economic policy will support theindustrial sector in Indonesia and its role on economic growth.Keywords: Industrialization, Political Economy and Economic Policy